Locomotor system morphological changes study: body posture versus obesity - Bankoff, Antonia Dalla Pria (2008)
The locomotor system morphological changes related to obesity were studied in 19 subjects of both sexes. They were divided into 03 groups as follows: G1 = 03 (male individuals), G2 = 04 and G3 = 12 (female subjects). The data were collected by a computerized Postural Evaluation System (Micromed Biotechnology) from the Laboratory of the Electromyography and Postural Evaluation-FEF/UNICAMP. Results: a greater incidence of fallen shoulders was detected in the female group in comparison with the male one. Group 02 registered a significant elbow morphological change. Body fat concentration on the posterior gluteus region was greater to G1, whereas in G2 and G3 the greater concentration was observed in the lateral gluteus region. There was an incidence of postural deviations such as: cervical lordosis, kyphosis, hyperlordosis, increased sacrum convexity, pelvic inclination, excessive increase in abdomen region and reduction of the distance between the external auditory meatus and shoulders.